Traditional Weaver Productivity: Why Experience Outweighs Skill for Mandar Silk Weavers in West Sulawesi? - Eny Afrilia; Wahdaniah Wahdaniah; Anis Anshari Mas’ud (Jambura Science of Management, 2026)
Purpose: This study aims to determine the influence of skills and work experience on the productivity of weavers in Lego Village.Design/Methodology/Approach: This study employed purposive sampling to select 51 Mandar silk weavers from Lego Village, representing 51% of the total population, based on predefined criteria for skill and experience.Findings: The results of this study indicate that skills do not significantly affect work productivity, whereas work experience does. However, skills and work experience simultaneously influence work productivity. These findings emphasize the importance of an experiential approach to training and policy for the preservation of traditional weaving, which affects cultural preservation, economic growth, and knowledge transfer.